Effect of Volatile Boron Species on the Electrocatalytic Activity of Cathodes of Solid Oxide Fuel Cells: III. Ba0.5Sr0.5Co0.8Fe0.2O3-δ Electrodes - Chen, Kongfa; Hyodo, J.; O'Donnell, Kane; Rickard, William; Ishihara, T.; Jiang, San Ping (The Electrochemical Society, Inc, 2014)
The effect of volatile boron species on the electrocatalytic activity, microstructure and phase stability of Ba0.5Sr0.5Co0.8Fe0.2O3-d (BSCF) cathodes has been studied. The cathodes were heat-treated at 800?C for 7 days in air in the presence of boron species vaporized from borosilicate glass, and were characterized by EIS, SEM, AFM, SIMS, XRD, XPS and ICP-OES. The results have shown that after the heat-treatment in the presence of borosilicate glass, boron deposition occurs mainly on the region near electrode surface, leading to the significant Ba and in particular Sr segregation, microstructure change and phase decomposition. On the other hand, the microstructure of the inner electrode layer is almost intact. Electrode polarization resistance, RE, of an as-prepared BSCF cathode is 0.93 and 0.23 Q cm2 at 650 and 800?C, respectively, and changes to 2.08 and 0.15 Q cm2 after heat-treatment at 800?C for 7 days in the presence of borosilicate glass, respectively. The increase in RE for the O2 reduction reaction on BSCF is much lower than that observed on La0.6Sr0.4Co0.2Fe0.8O3-d (LSCF) cathodes, indicating that BSCF cathodes have a much better tolerance toward boron deposition and poisoning. The limited attack of volatile boron species on BSCF is most likely related to the much slower kinetics of the formation of strontium and barium borates as compared to the formation of lanthanum borates. This study provides a significant insight into design and development of better contaminant-tolerant cathode materials for durable solid oxide fuel cell (SOFC) technologies.